Automated Step Detection in Inertial Measurement Unit Data From Turkeys - Bouwman, Aniek; Savchuk, Anatolii; Abbaspourghomi, Abouzar; Visser, Bram (Frontiers in Genetics, 2020)
Locomotion is an important welfare and health trait in turkey production. Current breeding values for locomotion are often based on subjective scoring. Sensor technologies could be applied to obtain objective evaluation of turkey gait. Inertial measurement units (IMU) measure acceleration and rotational velocity which makes them attractive devises for gait analysis. The aim of this study was to compare three different methods for step detection from IMU data from turkeys. This is an essential step for future feature extraction for the evaluation of turkey locomotion. Data from turkeys walking through a corridor with IMUs attached to each upper leg were annotated manually. We evaluated change point detection, local extrema approach, and gradient boosting machine in terms of step detection and precision of start and end point of the steps. All three methods were successful in step detection, but local extrema approach showed more false detections. In terms of precision of start and end point of steps, change point detection performed poorly due to significant irregular delay, while gradient boosting machine was most precise. For the allowed distance to the annotated steps of 0.2s, the precision of gradient boosting machine was 0.81 and the recall was 0.84, which is much better in comparison to the other two methods (<0.61). At an allowed distance of 1s performance of the three models was similar. Gradient boosting machine was identified as the most accurate for signal segmentation with final goal to extract information about turkey gait, however it requires an annotated training dataset.